The Wonder Dough (Analytic Teaching, 1988)
Introduction:  One afternoon, Mark and Deena came rushing into the kitchen shouting, "Mom, we're hungry - what do you have for tea?"  Mommy smiles.  "Not much really - but I have a surprise for you, anyway.  Look at the table!"  Mark and Deena look at the table.  There they see a big bowl.  "What is it?" Deena asks.  "It's dough.  It must rise, then I'll bake some buns for you."